Penerapan Search Engine Optimazation untuk Optimasi Performa Konten Pada Website Kampus - Anggra Triawan; An Nissa Pujiantina Majid (TeknoIS : Jurnal Ilmiah Teknologi Informasi dan Sains, 2023)
The use of content on the campus website that is still static, using a single meta tag, and not applying meta writing techniques causes the content on the website to be not optimal and the use of meta tags, headings and subheadings in website content is not yet effective, so optimization on page optimization is still weak. Search Engine Optimization (SEO) is a way to optimize a website so that it ranks at the top of search results. On Page Optimization is a technique for optimizing content on website pages. This study applies Search Engine Optimization On Page to optimize content on the Binaniaga Indonesia University website. The results of the measurements carried out for one week obtained the final result measurement of 3.59, the average number of persession pages from 5 users, with an increase of 41.78% after implementing Search Engine Optimization. So that the developed application can be categorized into a very feasible interpretation.